Ulitníky pseudokrasovej tiesňavy Parkaň v pohorí Bachureň na východnom Slovensku - Jakub Repaský; Dagmar Říhová; Kateřina Kubíková; Radovan Coufal; Jan Oravec; Lucie Juřičková (Malacologica Bohemoslovaca)
A pseudokarst gorge with the local name „Parkaň“ is located near the village of Renčišov in the Bachureň Mountains. This area was surveyed in 2023. In total, we recorded 52 species of terrestrial gastropods. These were predominantly forest species (38; 73%), euryvalent species were less represented (13; 25%), and one open country species was also found (1; 2%). The local microtopographic diversity (moist rubble, rock walls covered with moss, dead wood) with historic habitat continuity support the high species diversity of the gastropod fauna. The results highlight the conservation importance of the area and the presence of sensitive species such as Argna bielzi, Macrogastra tumida, Pseudalinda stabilis and Bulgarica cana, indicating the well-preserved state of the habitat. This area represents a local diversity hotspot surrounded by mostly disturbed production forest monocultures. The discovery of one, slightly damaged shell of the species Helicigona lapicida is interesting. Since we could not find live individuals, we do not consider this finding a reason to include the species in the malacofauna of Slovakia.